PENGARUH KOMBINASI LARUTAN IRIGASI TERHADAP KEKUATAN PELEKATAN SEALER RESIN DAN NON-RESIN PADA DINDING SALURAN AKAR - Amalia Mahpudhah; Isyana Erlita; Buyung Maglenda (Universitas Lambung Mangkurat, 2021)
ABSTRACTBackground:Resin-based sealers are widely used because they have good physical and biological properties and form micro-retention in dentin. There are also non-resin-based sealers. A non-resin-based sealer also has good micro-retention properties. The bond between dentin and the sealer can be improved by removing the smear layer. 2.5% NaOCl and 17% EDTA are the most common combination of irrigation solutions used to remove the smear layer. The use of 2% chlorhexidine after 17% EDTA at the end of irrigation will increase the antimicrobial effect and inhibit the activity of matrix metallo-proteinase (MMP).Objective: to determine push-out bond strength of obturation material with resin and non-resin sealers with 2.5% NaOCl, 17% EDTA and 2% CHX irrigation solution.Methods: The study used a true experimental method (post-test only group design). The treatment group (obturation with gutta percha and resin sealer; gutta-percha and non-resin sealer; gutta-percha only) were tested using a universal testing machine. Statistical tests using the Kruskal Wallis test and Mann Whitneytest.Results:Kruskall Wallis test showed that there were differences value of push-out bond strength in different obturation material with gutta percha and resin sealer; gutta-percha and non-resin sealer; gutta-percha only (p <0.05). The Mann Whiney test showed a significant difference bond strength between the non-resin sealer obturation group and gutta percha only group and between between the resin sealer obturation group and gutta percha only group (p<0.05).Conclusion:The use of sealer (a resin-based sealer and non-resin-based sealer) and 2.5% NaOCl, 17% EDTA and 2% CHX as irrigation solution can increase the bond strength of the obturation material. Keywords:bond strength, non-resin based sealer, resin based sealer. ABSTRAKLatarbelakang:Sealerberbahandasar resin banyakdigunakankarenadapatmembentukretensimikro pada dentin. Sealer non-resin juga memilikisifatretensimikro yang baik. Ikatan dentin dan sealerdapatditingkatkandenganmenghilangkansmear layer. NaOCl 2,5% dan EDTA17% adalahkombinasilarutanirigasi yang umumdigunakan. Penggunaanchlorhexidine 2% setelah EDTA 17% pada akhiririgasiakanmeningkatkanefekantimikroba dan menghambataktivitasmatrix metallo-proteinase (MMP). Tujuan:untukmenentukankekuatanikatanpush-outsealer resin dan non-resin denganNaOCl 2,5%, EDTA 17% dan CHX 2%. Metode:Penelitianinimenggunakanmetodeeksperimenmurni (post-test only group design). Kelompokperlakuan (gutta percha dan sealer resin; gutta percha dan sealer non-resin; gutta perchasaja) diujimenggunakanuniversal testing machine. Uji statistikmenggunakan uji Kruskal Wallis dan uji Mann Whitney. Hasil: Uji Kruskall Wallismenunjukkanadaperbedaannilaikekuatanperlekatanpush-outbahanobturasi yang berbedadengangutta percha dan sealer resin; gutta-percha dan sealer non-resin; hanyagutta-percha (p <0,05). Uji Mann Whitneymenunjukkanperbedaankekuatanperlekatan yang signifikanantarakelompoksealer non-resin dibandingkankelompoktanpasealer dankelompoksealer resin dibandingkankelompoktanpasealer (p <0,05). Kesimpulan:Penggunaansealer dan penggunaanNaOCl 2,5%, EDTA 17%, dan 2% CHX sebagailarutanirigasidapatmeningkatkankekuatanperlekatanbahanobturasi. Kata kunci:kekuatanperlekatan, sealer non-resin, sealer resin.